2021
DOI: 10.1097/spc.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

Metastasectomy in kidney cancer: current indications and treatment approaches

Abstract: Purpose of reviewAlthough systemic agents for the treatment of metastatic renal cell carcinoma (mRCC) have improved survival, remission and cure for mRCC remains rare with systemic therapy alone. However, there is a body of observational evidence supporting a survival benefit in mRCC among patients who undergo complete surgical consolidation including resection of the primary tumor and all metastatic deposits. In this review, we aim to synthesize recent evidence regarding metastasectomy (MTS), with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A previous study indicated a role for metastatectomy or resection when there is a solitary bone lesion from RCC, because it is associated with an overall survival advantage [6]. However, it is impossible to discern to what degree these findings are biased by favorable tumor biology and patient selection, as opposed to being related to surgical metastatectomy [11]. What needs further evaluation with larger-scale studies is whether more-aggressive resection is beneficial to implant survival and/or patient survival.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study indicated a role for metastatectomy or resection when there is a solitary bone lesion from RCC, because it is associated with an overall survival advantage [6]. However, it is impossible to discern to what degree these findings are biased by favorable tumor biology and patient selection, as opposed to being related to surgical metastatectomy [11]. What needs further evaluation with larger-scale studies is whether more-aggressive resection is beneficial to implant survival and/or patient survival.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…Moreover, there was no difference in survival between patients with progression and those without. Based on these findings, surgeons might give special consideration to the type of resection (curettage, en bloc, or intralesional) in addition to whether to use intramedullary versus other stabilization for patients who present with RCC bone metastases [3,6,11,12].…”
mentioning
confidence: 99%
“…For instance, Singla et al demonstrated improved overall survival for patients with metastatic clear cell RCC for those undergoing a cytoreductive nephrectomy (CN) with immunotherapy treatment versus immunotherapy alone (16). Furthermore, it has been shown that metastasectomy can also offer durable survival benefit (17,18). Surgical resection may be beneficial given that bulky tumors can inhibit immune responses that are vital to combating cancer (19).…”
Section: Introductionmentioning
confidence: 99%
“…As novel treatment paradigms continue to emerge, it is clear that one size fits all model is not ideal. As Prunty et al [1] demonstrate it appears that some patients may benefit from metastasectomy -but whom? We also know that a subset of patients with MIBC can be rendered disease free with radical transurethral resection of bladder tumor, chemoradiotherapy or a combination thereof -but how do we select for these patients and avoid the morbidity of radical cystectomy?…”
mentioning
confidence: 99%
“…In this issue of Current Opinion in Supportive and Palliative Care , experts in the field of urologic oncology discuss current treatment approaches to various urological malignancies. Prunty et al [1] discuss the role of metastasectomy in advanced kidney cancer. Randomized control data are lacking and are unlikely to ever come to fruition given the rarity of this entity, leaving clinicians to make decisions based on expert opinions and retrospective population-based data.…”
mentioning
confidence: 99%